Renal Cell Carcinoma With Extensive Tumor Thrombus Into the Inferior Vena Cava and Right Atrium in a 70-Year-Old Man. Issue 3 (3rd May 2019) - Oltean, Monica-Alexandra; Matuz, Roxana; Sitar-Taut, Adela; Mihailov, Anca; Rednic, Nicolae; Tantau, Alina; Toganel, Razvan; Minciuna, Ioan-Alexandru; Orasan, Olga; Muresan, Flaviu; Cozma, Angela
The case of a male patient is reported, who presented with renal carcinoma and tumor thrombus in the inferior vena cava (IVC) extending from the right atrium (RA) to the bifurcation of IVC, common and external right iliac vein thrombosis, common and deep right femoral vein thrombosis, right popliteal vein thrombosis, with pulmonary and hepatic metastasis, treated with sorafenib. Renal cell carcinoma (RCC), the most common form of kidney cancer, occurs in 90% of cases and is nearly twice as common in men as in women. The diagnosis of RCC is accompanied by intravascular tumor thrombus in 10% of cases, and further extension of the tumor reaching RA is detected in approximately 1% of all patients. Therapy for advanced renal cell cancer has evolved considerably in the past decade, with new agents greeted like "buried treasure." Before 2005, the widely used systemic agents were cytokine interferon alfa and interleukin-2, which yielded modest efficacy and substantial toxicity. Tyrosine kinase inhibitors (TKIs) increase progression-free survival and/or overall survival as both first-line and second-line treatments for metastatic RCC. Sorafenib is an oral multikinase inhibitor with activity against Raf-1 serine/threonine kinase, B-Raf, vascular endothelial growth factor receptor-2 (VEGFR-2), platelet-derived growth factor receptor (PDGFR), FMS-like tyrosine kinase 3 (FLT-3), and c-KIT.